The curse of king tut's mummy ebook - Zoehfeld, Kathleen Weidner (Stepping Stones., 2009)
When the pharoahs of Egypt died, they were mummified and buried in pyramids and tombs with all their riches. But as centuries passed, the tombs were looted and the pharoahs' gold stolen. Then Howard Carter found the greatest Egyptian treasure trove of all—the tomb of King Tut's mummy! But did the amazing treasure come with a deadly curse?